Conditions for professional digital competence: the teacher educators’ view - Maria Lindfors (Taylor & Francis Group, 2021)
This study explores how Swedish teacher educators view individual, collegial, and organisational conditions framing the fulfilment of their dual didactical task, which is to use digital technology in a way that ensures student teachers graduate from teacher education (TE) with the professional digital competence (PDC) needed for their future working lives in a digitalised school. Using a purposive sampling approach, we used thematic coding to analyse 13 semistructured interviews with teacher educators representing 21 mandatory courses in educational science at one teacher education institution in Sweden. The findings cover aspects of the teacher educators’ PDC, how to act as a digital role model for the student teachers, support in educational policy and assignments, and the possibilities for participating in continuous professional development (CPD) in PDC. This study demonstrates an urgent need to improve conditions for successful fulfilment of teacher educators’ dual didactical task. For example, TE policy requires a strong focus on digital technology and PDC. CPD activities should be easy to access in order for teacher educators to develop their PDC. Moreover, leaders at the organisational level in TE institutions should acknowledge and place higher value on teacher educators’ work to digitalise educational practices.